Preparation and characterization of poly(methyl methacrylate) and poly(maleic anhydride-co-diallyl phthalate) grafted carbon black through γ-ray irradiation. (February 2016) - Bo, Yang; Cui, Jiayang; Cai, Yangben; Xu, Shiai
Abstract: In this study, the grafting polymerization of methyl methacrylate (MMA) monomer and maleic anhydride/diallyl phthalate (MAH/DAP) co-monomer onto the surface of carbon black (CB) were carried out at room temperature and normal pressure by γ-ray irradiation. The surface chemistry of grafted CBs were characterized by infrared spectroscopy (IR), thermo-gravimetric analysis (TGA) and X-ray photoelectron spectroscopy (XPS). The results show that there are some remanent polymers on the surface of modified CBs after extract for 48 h, indicating that poly(methyl methacrylate) (PMMA) and poly(MAH-co-DAP) have been successfully grafted onto the surface of CB without using initiator due to the high energy of γ-ray irradiation. Dynamic light scattering (DLS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) reveal that the grafted CBs have smaller average aggregate size and better dispersibility than that of CB in absolute ethanol. In addition, it was found that the amount of oxygen groups and the irradiation doses/dose rates have little effect on the grafting degree of CB. Highlights: The influence of monomer activity on the grafting of CB was investigated. Methyl methacrylate was grafted onto CB surface through γ-ray irradiation. Diallyl phthalate was used to assist grafting of maleic anhydride onto CB surface. The grafted CBs have smaller size and better dispersibility.